The Impact Of Self-Control And Lifestyle On Sharia Financial Behavior With Religiosity As A Moderating Variable Among Young Workers In Klaten - Hadi, Abdul (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze the impact of self-control and lifestyle on Sharia financial behavior with religiosity as a moderating variable among young workers in Klaten. The method used in this research is a quantitative approach utilizing a questionnaire as the data collection instrument. Data analysis was performed using the path analysis method. The results of the study indicate that self-control and lifestyle have a positive and significant impact on Sharia financial behavior. Additionally, religiosity significantly moderates the relationship between self-control and Sharia financial behavior. However, religiosity does not significantly moderate the relationship between lifestyle and Sharia financial behavior. These findings suggest that self-control and lifestyle play crucial roles in shaping Sharia financial behavior, with the influence of self-control being stronger when religiosity is high. Therefore, increasing financial literacy and strengthening religious values among young workers is essential to promote wiser financial behavior in line with Sharia principles.